2021
DOI: 10.1017/s1355617721000679
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Neuropsychological Assessment by Videoconference and Face to Face

Abstract: Objective: To compare the administration of neuropsychological tests by teleneuropsychology (TeleNP) and face to face (F-F) in order to determine the feasibility and reliability of TeleNP. Method: At the inclusion visit, all participants underwent a traditional F-F neuropsychological assessment as part of their standard care. Four months after inclusion, they were randomized to undergo an additional neuropsychological assessment either by F-F administration or by TeleNP. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…The study aimed to provide normative data of neuropsychological memory tests performed via videoconference. Several studies described videoconferencing assessments as similar to face-to-face settings [ 6 , 18 , 21 , 24 , 44 ]. The remote setting could expose to many risks and limitations [ 17 , 18 ], as much as several benefits [ 10 , 13 ]: (i) covering long distances; (ii) patients with motor deficits can perform a neuropsychological assessment at their place and maintaining continuity in health and care during emergencies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study aimed to provide normative data of neuropsychological memory tests performed via videoconference. Several studies described videoconferencing assessments as similar to face-to-face settings [ 6 , 18 , 21 , 24 , 44 ]. The remote setting could expose to many risks and limitations [ 17 , 18 ], as much as several benefits [ 10 , 13 ]: (i) covering long distances; (ii) patients with motor deficits can perform a neuropsychological assessment at their place and maintaining continuity in health and care during emergencies.…”
Section: Discussionmentioning
confidence: 99%
“…Analysing in detail, most of these studies adapted verbal task tests, such as the Digits Span Forward and Backward, the Boston Naming Test [ 6 , 20 ], and the Hopkins Verbal Learning Test [ 18 ] in adults and senior adults. In a study [ 21 ] carried out in a French memory clinic, patients performed a neuropsychological evaluation two times (i.e., face-to-face and teleneuropsychology). The second assessment took place 4 months later, adopting parallel versions of neuropsychological tests.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many recent publications have shown the validity of videoconference neuropsychological testing compared to face-to-face testing [8][9][10]. A review paper by Marra and collaborators [10] suggests that the remote administration of the MoCA shows good validity compared to its face-to-face administration.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that administering these assessments using telecommunication software provided a valid alternative to face‐to‐face assessments. A study of 150 adults by Gnassounou et al (2021) also found no difference between face‐to‐face and virtual administration of a brief neuropsychological assessment battery composed of the MMSE (Folstein et al, 1975), Free and Cued Selective Reminding Test (French version; Van der Linden et al, 2004), Mahieux Gestural Praxis Battery (Mahieux‐Laurent et al, 2009), Frontal Assessment Battery (Dubois et al, 2000), Trail Making Test (TMT; completion time and errors for part B; Godefroy et al, 2010), Rey–Osterreith Complex Figure (Meyers & Meyers, 1995) and Categorical and Phonological Verbal Fluency Tests (Godefroy et al, 2010). They did however identify small significant differences in the Digit Span Forwards and Backwards (Wechsler, 2008) and the number of errors on the TMT part A (Godefroy et al, 2010).…”
Section: Introductionmentioning
confidence: 99%